Influence of sizes of rubber particles in latex on mechanical properties of natural rubber filled with carbon black. (18th November 2022) - He, Simin; Zhang, Fuquan; Liu, Shuo; Cui, Haipeng; Chen, Song; Peng, Wenfeng; Chen, Guojing; Liao, Xiaoxue; Liao, Lusheng
Abstract: The structures and properties of natural rubber (NR) obtained from latex with small and large rubber particles (SRP and LRP) are obviously different, while carbon black (CB)/SRP or CB/LRP composites have rarely been reported. In this work, SRP and LRP are separated from natural rubber latex (NRL). The properties of obtained NR/CB composites are systematically investigated as a function of SRP and LRP mass ratios. It shows that the nitrogen content of SRP (1.32%) is much higher than that of LRP (0.10%). Mechanical properties increase with the increase of LRP content because plenty of agglomerates exist in SRP/CB composite whereas LRP/CB composite shows a homogeneous dispersion. Furthermore, a possible model is proposed to illustrate the transformations of agglomerates during stretching and dynamic compressing process. This study provides a new perspective for the design of NR materials through the selection of rubber particles in NRL. Graphical abstract: Image 1 Highlights: The cure characteristics of carbon black filled natural rubber vulcanizates increase with the increase of SRP content. LRP composite shows highest tensile properties and fatigue life as well as lowest compression set and temperature rise. The carbon black in LRP composite shows homogeneous distribution, while SRP composite contains lots of agglomerates. The agglomerates in SRP composite form stress and heat concentration during tensile and dynamic compressing process.